A Platform for Preparation of Monodispersed Fluorescent Conjugated Polymer Microspheres with Core‐Shell Structures. Issue 1 (1st October 2012) - Wang, Shangli; Zhao, Wei; Song, Jing; Cheng, Si; Fan, Li‐Juan
Abstract A strategy to prepare stable monodispersed fluorescent microspheres is developed by modifying the Wessling method to synthesize poly(p‐phenylenevinylene) (PPV) on the surface of a highly crosslinked polymer core. The positively charged PPV polymer precursors (pre‐PPV) are adsorbed onto the core with negative charges on the surface and then the insoluble fluorescent PPVs form after thermal elimination. Each individual sphere is found to possess a very smooth surface with an even distribution of fluorescence by microscopic techniques. Very small coefficient of variance (CV) values of emission intensity (<4.0%) and size (<2.3%) are realized for microspheres prepared in the same batch. The spheres are demonstrated to have good thermal stability and photostability.